Cross-sectional internet survey exploring women's knowledge, attitudes and practice regarding urinary tract infection-related symptoms in the Netherlands. Issue 5 (18th May 2022) - Cox, Stefan Martinus Leonardus; van Hoof, Minke W E M; Lo-A-Foe, Kelly; Dinant, Geert-Jan; Oudhuis, Guy J; Savelkoul, Paul; Cals, Jochen W L; de Bont, Eefje G P M
Abstract : Objectives: Urinary tract infections (UTIs) are the most prevalent cause for women to consult a general practitioner (GP) and are commonly treated with (broad-spectrum) empirical antibiotics, even though 50% of UTIs are self-limiting. In this study, we aim to explore women's attitudes and experiences regarding UTIs, in order to determine patients' willingness to accept delayed antibiotic prescriptions. Design: An internet-based cross-sectional survey Setting: We recruited participants during 2 weeks of March and April in 2020 through several social media platforms. Participants: We obtained 1476 responses, of which 975 were eligible for analysis. Results: We asked women about their knowledge, attitudes and practice regarding UTI-related symptoms. Participants ranked 'confirmation of diagnosis' (43.8%) as the most important reason to consult a GP with urinary symptoms, followed by 'pain relief' (32%), and 'antibiotic prescription' (14.3%). For treatment, 71% of participants reported that their GP prescribed immediate antibiotics, while only 3% received a delayed antibiotic prescription and 1% was advised pain medication. Furthermore, 50% of respondents were aware of the possible self-limiting course of UTIs and 70% would be willing to accept delayed antibiotic treatment, even if a certain diagnosis of UTI was established. Willingness to delay was lower in experienced patients compared to inexperienced patients. Conclusions: Women are quite receptive to delayed antibiotics as an alternative to immediate antibiotics for UTIs or urinary symptoms. GPs should consider discussing delayed antibiotic treatment more often with women presenting with urinary symptoms.